ANALYSIS OF THE INFLUENCE OF POVERTY, HUMAN DEVELOPMENT INDEX, AND POPULATION ON INCOME INEQUALITY IN NORTH SUMATRA 2018-2022 - Simbolon, Cinta Marito; Nisa, Fadila; Pinem, Haifa Azalia; Sinaga, Darwin; Tobing, Kristanto Lumban; Hidayat, Nasrullah (Quantitative Economics Journal, 2023)
This study seeks to investigate the extent to which income inequality in North Sumatra for the 2018-2022 period is impacted by poverty, the human development index (HDI), and population. It employs quantitative methods along with descriptive analysis. The data used for this research is derived from the North Sumatra Central Statistics Agency (BPS) and covers a four-year span from 2018 to 2022. The data analysis approach incorporates Fixed Effects, determined through the Chow test and Hausman test. The findings of this investigation reveal the following: (1) The independent variables, specifically poverty, HDI, and population, exert a significant influence on income inequality in the North Sumatra province. (2) Poverty has a negative impact on income inequality in North Sumatra, but not to a statistically significant extent. (3) The HDI variable shows a negative and statistically significant impact on income inequality in North Sumatra. (4) The Population variable shows a positive and statistically significant impact on income inequality in North Sumatra.